MANAJEMEN PROGRAM LITERASI BAGIAN PERPUSTAKAAN DALAM MENINGKATKAN MINAT BACA - Nurfitriah; Milahtul Latifah (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2022)
Islam is a religion that encourages to cultivate a culture of literacy among its people. This is inseparable from the history of the revelation of the Qur'an. So, the obligation to read has existed for a long time, various efforts have been made to improve literacy starting from writing activities, then using it to think about what is read. However, the current problem is that the literacy skills of students in Indonesia are quite good and not too low. The problem at Darussalam Islamic Boarding School is that students still do not have high reading interest due to any factors. The aim is to find out management of the library's literacy program in increasing student interest in reading at the Darussalam Islamic Boarding School, Bogor. This study uses qualitative research, with a qualitative descriptive research design format. The results of his research, namely the management is quite good because it is based on the work program that was made during the work deliberation session. The literacy programs include: reading and writing activities, writing articles, scientific competitions, procurement of mobile libraries and so on to make them as interesting as possible. Because, the majority of students have low reading interest where these students use various reasons so that they spend more time on other activities in the afternoon, both deepening lessons for students who are lacking in cognitive aspects and have not been able to regulate affective aspects that can arise from activities that generate interest